Friedman based analysis of perceived constraints among dairy farmers affected by national calamity in India - Lal, Sudhanand Prasad; Kadian, Kehar Singh; Kale, Rajiv Baliram; Shruti, Shruti (Indian Journal of Dairy Science, 2016)
The present study was conducted to study the perceived constraints faced by victims of the national calamity, i.e., Kosi flood that occurred in Bihar state of India way back on 18th August, 2008. Eight independent constraints were taken for the study based on secondary data and reconnaissance, which were later classified as 4 broad constraints. The study revealed that most severe constraint perceived by dairy farmers was ‘lack of knowledge regarding preparedness of natural calamity for livestock protection’. Asymptotic significance obtained from the Friedman test was 0.000 (p